Gene Expression Profiling of the Local Cecal Response of Genetic Chicken Lines That Differ in Their Susceptibility to Campylobacter jejuni Colonization - Li, Xianyao; Swaggerty, Christina L.; Kogut, Michael H.; Chiang, Hsin-I; Wang, Ying; Genovese, Kenneth J.; He, Haiqi; Zhou, Huaijun (PloS one, 2010)
Campylobacter jejuni (C. jejuni) is one of the most common causes of human bacterial enteritis worldwide primarily due to contaminated poultry products. Previously, we found a significant difference in C. jejuni colonization in the ceca between two genetically distinct broiler lines (Line A (resistant) has less colony than line B (susceptible) on day 7 post inoculation). We hypothesize that different mechanisms between these two genetic lines may affect their ability to resist C. jejuni colonization in chickens. The molecular mechanisms of the local host response to C. jejuni colonization in chickens have not been well understood. In the present study, to profile the cecal gene expression in the response to C. jejuni colonization and to compare differences between two lines at the molecular level, RNA of ceca from two genetic lines of chickens (A and B) were applied to a chicken whole genome microarray for a pair-comparison between inoculated (I) and non-inoculated (N) chickens within each line and between lines. Our results demonstrated that metabolism process and insulin receptor signaling pathways are key contributors to the different response to C. jejuni colonization between lines A and B. With C. jejuni inoculation, lymphocyte activation and lymphoid organ development functions are important for line A host defenses, while cell differentiation, communication and signaling pathways are important for line B. Interestingly, circadian rhythm appears play a critical role in host response of the more resistant A line to C. jejuni colonization. A dramatic differential host response was observed between these two lines of chickens. The more susceptible line B chickens responded to C. jejuni inoculation with a dramatic up-regulation in lipid, glucose, and amino acid metabolism, which is undoubtedly for use in the response to the colonization with little or no change in immune host defenses. However, in more resistant line A birds the host defense responses were characterized by an up-regulation lymphocyte activation, probably by regulatory T cells and an increased expression of the NLR recognition receptor NALP1. To our knowledge, this is the first time each of these responses has been observed in the avian response to an intestinal bacterial pathogen.